Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams How the Age Groups Shift 1911 [Picture] 1931 [Picture] 1951 [Picture] 1971 [Picture] Each complete symbol represents 2.5 million population green: youth blue: old age red: working age 43 15X/2/566/303